Tissue Engineering of Articular Cartilage (Al-Quds Journal for Natural Sciences, 2022)
Nehal Abu LailDepartment of Biomedical Engineering and Chemical Engineering, The University of Texas at San Antonio, San Antonio, TX, USAAbstractArticular cartilage (AC) is the tissue that wraps moving joints in the body. As a tissue, it provides lubrication as well as load bearing in some joints. The tissue is subject to harsh chemical and mechanical environments in vivo and is characterized by being devoid of blood, nerve and lymph nodes. Upon injury, the tissue is incapable of healing. Damaged AC tissues mark the global disease of osteoarthritis (OA). As a pandemic, OA is prevalent worldwide and is ranked first for which patients seek treatments. Unfortunately, the disease has no current disease modifying drugs and it is only managed for symptomatic relief using pain killers, physical therapy and surgical procedures. In search for less invasive treatments, tissue engineering has been sought to provide the alternative. Tissue engineering refers to creation of eventually personalized tissues that can be used to replace damaged tissues in vitro. As an approach, it relies on seeding cells on scaffolds and incorporating the two in bioreactors that mimic the joint environment. Cells are then fed a medium with growth factors in it for a period of time until they form tissues. The tissues are then characterized to check if they represent the native tissue in structure and function. If not, the parameters used to engineer the tissue are revisited and the loop is repeated again. Here, tissue engineering of AC will be introduced. After that, the four pillars of tissue engineering (cells, scaffolds, growth factors, and bioreactors) will be discussed with questions that remain to be addressed. A section that discusses how engineered tissues are characterized will follow. Finally, the review ends with a summary of where the field is heading to realized quality AC tissues. This review is not meant to be comprehensive of existing literature.